If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -4 + -5x = -24 Reorder the terms: -4 + -5x + -5x = -24 Combine like terms: -5x + -5x = -10x -4 + -10x = -24 Solving -4 + -10x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -10x = -24 + 4 Combine like terms: -4 + 4 = 0 0 + -10x = -24 + 4 -10x = -24 + 4 Combine like terms: -24 + 4 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= | | 13x+1+12x+9= | | t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 | | 4/24 | | (-6)(-6)= | | 24/.4 | | 19=3t-23 | | 3(3m+4)-2(m-7)=0 | | 6d-18+2=2 | | 24/.04 |